POSITIONING ONLINE LEARNING AS A STRATEGIC ASSET IN THE THINKING OF UNIVERSITY PRESIDENTS AND CHANCELLORS - Smith, Samuel H. “Pete”; Smith, Samuel H.; Samors, Robert; Mayadas, Frank A. (Online Learning, 2008)
Online learning is becoming an increasingly popular way for students to take courses and for faculty to teach, with the number of students taking at least one online course growing more than ten times as rapidly as the head count enrollments in post-secondary education. Clearly, the time is right to reframe a national dialogue amongst the leaders of our traditional universities and colleges about this asset. Many of the earlier dialogues amongst presidents and chancellors relative to online learning focused on the quantity and, to a lesser extent, the quality of online instruction and its promised impact on our traditional campuses. Previously, online learning was also often associated with for-profit universities which to date remain in a growth phase and are developing academic acceptance.